2015
DOI: 10.1038/pcan.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

A molecular signature of PCA3 and ERG exosomal RNA from non-DRE urine is predictive of initial prostate biopsy result

Abstract: A novel molecular signature (EXO106 score) derived from non-DRE urine demonstrated independent, negative predictive value for the diagnosis of high-grade PCa from initial biopsy for men with 'gray zone' serum PSA levels. Its use in the biopsy decision process could result in fewer prostate biopsies for clinically insignificant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 39 publications
3
136
0
8
Order By: Relevance
“…Ряд авторов высказыва-ют предположение о том, что выделение и концентри-рование экзосом из мочи у больных РПЖ позволяют получить препарат, анализ экспрессии генов в котором даст более воспроизводимые результаты за счет обога-щения полученной тотальной РНК молекулами мРНК опухолевого происхождения. Сравнение уровней экс-прессии РСА3 в цельной моче, осадке и экзосомах у раз-ных авторов показывает противоречивые результаты: в одних диагностическая точность выявления РПЖ вы-ше при анализе мочи, в других -при анализе экзосом, полученных из мочи [11,13,14].…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
See 1 more Smart Citation
“…Ряд авторов высказыва-ют предположение о том, что выделение и концентри-рование экзосом из мочи у больных РПЖ позволяют получить препарат, анализ экспрессии генов в котором даст более воспроизводимые результаты за счет обога-щения полученной тотальной РНК молекулами мРНК опухолевого происхождения. Сравнение уровней экс-прессии РСА3 в цельной моче, осадке и экзосомах у раз-ных авторов показывает противоречивые результаты: в одних диагностическая точность выявления РПЖ вы-ше при анализе мочи, в других -при анализе экзосом, полученных из мочи [11,13,14].…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
“…На основе данных мульти-центровых исследований в настоящее время пороговое значение уровня ПСА определено Европейской ассо-циацией урологов как 2,5 нг/мл со скоростью прироста ОНКОУРОЛОГИЯ 3'2017 ТОМ 13 CANCER UROLOGY 3'2017 VOL. 13 …”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
“…Other studies demonstrated the presence of both TMPRSS2:ERG and PCA3 in EV fractions from the urine of PCa patients (67,69). In a recent study, a molecular signature (EXO106 score), which is based on the combined normalized expression of ERG and PCA3 isolated with exosomes from urine samples from a cohort of 195 patients, was used to predict PCa (91). It should be noted that the methodology for exosome isolation in this study does not exclude the presence of sources other than exosomes.…”
Section: Prostasome-associated Pca Protein Markers In Bloodmentioning
confidence: 99%
“…For instance, we published an important paper on the role of ERG in prostate cancer [10]. More recently, several papers have highlighted that molecular signatures-either in the urine [11] or in the tumor [12] can be used to predict either risk of prostate cancer or metastases, respectively. Indeed, given the growth in molecular signatures for prostate cancer, we also published a helpful review for clinicians [13].…”
mentioning
confidence: 99%